Fabrication of high-quality two-dimensional electron gases by overgrowth of focused-ion-beam-doped AlxGa1−xAs - Reuter, D.; Riedesel, C.; Schafmeister, P.; Meier, Cedrik; Wieck, A. D. (Applied Physics Letters)

Magnetism and interface properties of epitaxial Fe films on high-mobility GaAs/Al0.35Ga0.65As(001) two-dimensional electron gas heterostructures - Cuenya, B. Roldan; Doi, M.; Keune, W.; Hoch, S.; Reuter, Dirk; Wieck, A.; Schmitte, T.; Zabel, H. (Applied Physics Letters)

Self-induced transparency in InGaAs quantum-dot waveguides - Schneider, S.; Borri, P.; Langbein, W.; Woggon, U.; Förstner, Jens; Knorr, A.; Sellin, R. L.; Ouyang, D.; Bimberg, D. (Applied Physics Letters)
We report the experimental observation and the theoretical modeling of self-induced-transparency signatures such as nonlinear transmission, pulse retardation and reshaping, for subpicosecond pulse propagation in a 2-mm-long InGaAs quantum-dot ridge waveguide in resonance with the excitonic ground-state transition at 10 K. The measurements were obtained by using a cross-correlation frequency-resolved optical gating technique which allows us to retrieve the field amplitude of the propagating pulses.
Keywords: tet_topic_qd

Two- and three-dimensional photonic crystals made of macroporous silicon and liquid crystals - Mertens, Guido; Röder, Thorsten; Matthias, Heinrich; Marsmann, Heinrich; Kitzerow, Heinz-Siegfried; Schweizer, Stefan L.; Jamois, Cecile; Wehrspohn, Ralf B.; Neubert, Mary (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Beam steering in waveguide arrays - Pertsch, T.; Zentgraf, Thomas; Peschel, U.; Bräuer, A.; Lederer, F. (Applied Physics Letters)

Control of the confining potential in ballistic constrictions using a persistent charging effect - Fischer, S. F.; Apetrii, G.; Skaberna, S.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Fabrication of quantum point contacts by engraving GaAs/AlGaAs heterostructures with a diamond tip - Regul, J.; Keyser, U. F.; Paesler, M.; Hohls, F.; Zeitler, U.; Haug, R. J.; Malavé, A.; Oesterschulze, E.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

A multipurpose torsional magnetometer with optical detection - Schaapman, M. R.; Christianen, P. C. M.; Maan, J. C.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Increased thermal budget for selectively doped heterostructures by employing AlAs/GaAs superlattices - Reuter, Dirk; Meier, C.; Álvarez, M. A. Serrano; Wieck, A. D. (Applied Physics Letters)

Influence of iron–silicon interaction on the growth of carbon nanotubes produced by chemical vapor deposition - de los Arcos de Pedro, Maria Teresa; Vonau, F.; Garnier, M. G.; Thommen, V.; Boyen, H.-G.; Oelhafen, P.; Düggelin, M.; Mathis, D.; Guggenheim, R. (Applied Physics Letters)

Shift of the photonic band gap in two photonic crystal/liquid crystal composites - Mertens, Guido; Röder, Thorsten; Schweins, Ralf; Huber, Klaus; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Increased thermal budget for selectively doped heterostructures by employing AlAs/GaAs superlattices - Reuter, Dirk; Meier, Cedrik; Álvarez, M. A. Serrano; Wieck, A. D. (Applied Physics Letters)

Azimuthal surface gliding of a nematic liquid crystal - Vorflusev, V. P.; Kitzerow, Heinz-Siegfried; Chigrinov, V. G. (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Gray‐scale in polymer‐stabilized antiferroelectric liquid crystal displays - Strauss, J.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Bulk‐induced alignment of nematic liquid crystals by photopolymerization - Jain, Sukhmal C.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Linear electro‐optic effects in polymer‐dispersed ferroelectric liquid crystals - Kitzerow, Heinz-Siegfried; Molsen, Henning; Heppke, Gerd (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)